1992
DOI: 10.1136/emj.9.2.230
|View full text |Cite
|
Sign up to set email alerts
|

Irregular discharge against medical advice from the accident and emergency department--a cause for concern.

Abstract: SUMMARYAn irregular discharge (ID) from the A&E department is an undesirable, but relatively common occurrence. A prospective study was undertaken to quantify the size of the problem and by arranging a subsequent review of the patient, to determine the clinical outcome.Over a 3-month period, 139 patients (0.73% of attendances) took their own discharge against medical advice. A further 566 patients (3.03% of attendances) left prematurely prior to any medical assessment (DNW).Attenders irregularly discharged, of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 5 publications
3
33
1
1
Order By: Relevance
“…It could also result in readmissions with longer hospital stays, prolonged illness and ultimately lead to higher costs of care. [12][13][14] The problem of DAMA has been reported in different countries worldwide. [1][2][3][4][5][6] However, this subject has rarely been studied in Arab countries, much less in Oman.…”
Section: 510mentioning
confidence: 99%
“…It could also result in readmissions with longer hospital stays, prolonged illness and ultimately lead to higher costs of care. [12][13][14] The problem of DAMA has been reported in different countries worldwide. [1][2][3][4][5][6] However, this subject has rarely been studied in Arab countries, much less in Oman.…”
Section: 510mentioning
confidence: 99%
“…In previous studies, DAMA patients were found to be young males from low socio-economic status groups and without health insurance (Ibrahim et al 2007;Nasir & Babalola 2008;Pennycook et al 1992). …”
Section: Discussionmentioning
confidence: 94%
“…Communication plays a major role in the provision of quality medical care. Inconsistency of information, unavailability of healthcare providers for enquiry or explanation, apathy, rudeness and unfriendly welcome have previously been shown to be contributing factors for DAMA (Pennycook et al 1992;Onukwugha et al 2010;Berger 2008).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] This study demonstrated that one person died and 85 patients needed further medical attention after self-discharge, hence from the viewpoint of risk management, ED need to be very concerned with this group of patients. These patients might warrant assessment by a senior doctor prior to their discharge in the first place.…”
Section: Discussionmentioning
confidence: 99%
“…There was also no established method nor resources in place to deal with this problem. 1,2 Patients discharged against medical advice might be expected to have more adverse consequences (exacerbation of illness, death, injury to self or others), [1][2][3] but information on this topic in Singapore was usually anecdotal. On one hand, selfdischarge might reflect problems in the care process in an ED.…”
Section: Introductionmentioning
confidence: 99%